PENGGUNAAN MODEL PROBLEM BASED INSTRUCTION DENGAN MEDIA KARTU PINTAR UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 47 KOTA JAMBI - Syuryani Syuryani. (Jurnal Pesona Dasar, 2019)
Science subjects need to be given to all students starting from elementary school to equip students with the ability to develop knowledge and understanding of science concepts that are useful and applicable in everyday life. Application of the Problem Based Instruction model is learning that involves the presentation of authentic and meaningful situations and serves as a basis for investigation and investigation for students. The formulation of the problem in this study is: Is the Problem Based Instruction model with smart card media able to improve science learning outcomes in third grade students of SD 47 / IV Jambi? From the results of data analysis, it was found that student learning achievement experienced an increase from cycle I to cycle III, namely, cycle I (67.65%), cycle II (76.62%), and cycle III (87.50%). The conclusion of this study is that Problem Based Instruction learning methods with Smart Card media can have a positive effect on learning motivation of Students of Jambi Elementary School 47 / IV Class III of Semester I 2018/2019 academic year and this learning model can be used as an alternative teaching field of study Natural Sciences.